Aku eks-tapol - Hersri S. (Hersri Setiawan) (Yogyakarta : Galang Press, 2003)
Author's account as a political ex-convict during the New Order government.
Koleksi Sumbangan : Dr. Syed Husin Ali.
Keywords: Hersri S; Political prisoners -- Indonesia -- Biography; Indonesia -- Politics and government -- 1966-1998.; Political persecution -- Indonesia